RECONSTRUCTING THE JUDICIAL SUPERVISION PARADIGM IN INDONESIA: ANALYSIS OF CONSTITUTIONAL COURT DECISION NO. 39/PUU-XIII/2015: REKONSTRUKSI PARADIGMA SUPERVISI DI INDONESIA: ANALISIS KEPUTUSAN MAHKAMAH KONSTITUSIONAL NO. 39/PUU-XIII/2015 - Arif Budiman; Firdaus Arifin (Pusat Studi Konstitusi dan Perundang-undangan, 2026)
This study examines fundamental weaknesses in judicial supervision in Indonesia following Constitutional Court Decision Number 39/PUU-XIII/2015. Using normative legal research with statutory, case-based, conceptual, and comparative approaches, the research identifies a critical research gap: the absence of comprehensive frameworks that integrate oversight of judicial technical reasoning with ethical evaluation in ways that maintain judicial independence while strengthening institutional accountability. This study theoretically contributes to the development of balanced independence-accountability theory by reconceptualizing judicial supervision as a system that enables rather than constrains judicial professionalism. The findings indicate three central issues. First, Constitutional Court Decision Number 39/PUU-XIII/2015 has significantly narrowed the authority of the Judicial Commission by restricting oversight related to judicial technical matters, creating institutional vulnerability. Second, both internal and external supervisory mechanisms failed to detect early indications of bribery in the acquittal verdict of Gregorius Ronald Tannur, despite striking inconsistencies between the court's legal reasoning and the evidentiary record, demonstrating critical gaps in monitoring systems. Third, judicial supervision in Indonesia remains predominantly reactive rather than proactive, addressing issues only after they surface in criminal proceedings. This study recommends regulatory reform through the enactment of the Judicial Office Bill, revision of the Judicial Commission Law, and integration of artificial intelligence systems with appropriate safeguards to identify anomalous judicial decisions. These measures aim to strengthen preventive mechanisms while preserving judicial independence and ensuring institutional accountability.